USE OF ALKALI ACTIVATED INCINERATION ASH AND COAL BASED FLYASH ALONG WITH PET BOTTLE STRIP REINFORCEMENT IN STABILIZING ROAD SUBGRADE SOIL - SHOFIUL AZAM, MOHAMMAD (Department of Civil Engineering, MIST, 2023)
The study presents a laboratory investigation on problematic soil stabilized by various combinations of alkali-activated medical waste based incineration ash (IA) and coal based flyash (FA). The PET bottle strips were added as a reinforcing agent to check further increments of strength and durability of the stabilized soil. Soil samples were prepared by the modified Proctor method at the optimum moisture content (OMC) and Geo-polymer contents (GPC) of 0, 5, 10, 15, and 20 percent. Unconfined compressive strength (UCS), and split tensile strength tests were conducted to evaluate the development of strength of the stabilized subgrade soil at a curing period of 14 and 28 days and after 24 hours of soaking. Again, soil mixed with incineration ash and fly ash, as above was then mixed with randomly distributed PET strips with 1, 1.5, and 2 percent, and UCS, split tensile strength, California bearing ratio (CBR), flexural strength, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) tests have been performed to determine the characteristics of problematic soil at a curing period of 28 days. It observed that, with the increase of geo-polymer content and aging, the strength of the soil increases four to five times and UCS was found to be linearly proportional. A maximum of 4032 kPa of UCS value was observed for 15% GPC with 1.5% PET, which is almost six times the untreated sample. The maximum retained strength for 28 days was found to be 82% for 15% GPC with a 1.5% PET strip; 15% GPC shows almost similar results approximately 64 to 82%. A maximum of 781 kPa was obtained for 20% GPC which is 2.76 times of 5% GPC in the split tensile strength test. CBR value shows significant improvement obtaining 145% with 15% GPC and 1.5% PET. Untreated soil depicted a higher axial strain of 7.5% and after treatment with Geo-polymer axial strain reduced i.e., increasing rigidity. During the soaked condition, the strain increases and gives a maximum value of 10% GPC and then gradually decreases. Microstructural analysis by SEM shows significant gel formation for 20% GPC over 5% GPC. EDS analysis also shows significant alkali activating bond with Geopolymer which is higher in 15% GPC over 5% GPC. The present study finds that geopolymer with addition of PET strips has the potential to improve the physical and engineering properties of subgrade soil significantly.